COMPARISION ANALYSIS OF ADJECTIVES IN ENGLISH AND UZBEK LANGUAGES - G'ulomjonova Sevinch Ilhom qizi; Muxamadiyev Aziz. Sh (PEDAGOGS, 2024)
Annotation. Adjectives describe how good or bad something is, its actions, behavior, uses, and clauses. helps to make the description of the object understandable when giving feedback or definition.